Pengaruh Economic Value Added dan Market Value Added terhadap Harga Saham pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2019-2022 - Lily Uly (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research aims to determine the influence of Economic Value Added (EVA) on share prices in banking companies, determine the influence of Market Value Added (MVA) on share prices in banking companies, determine the influence of Economic Value Added (EVA) and Market Value Added (MVA) on share prices in banking companies.